2010
DOI: 10.1590/s0365-05962010000600022
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Muckle-Wells em quatro membros de uma família

Abstract: Muckle-Wells syndrome is a rare autosomal dominant disease that belongs to a group of hereditary febrile syndromes. It is characterized by recurrent and self-limited episodes of fever, urticaria, arthralgia, myalgia and conjunctivitis since childhood, which are related to exposure to cold temperatures. Lately, progressive sensorineural hearing loss occurs. Amyloidosis is the main complication and can be found in about 25% of the cases. It has been demonstrated that there is an association with mutations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The study has identified 11 members of a single family with the clinical picture of MWS. The typical urticarial rash as a leading and the first symptom was present in all patients, similar to other reports (3, 12). Characteristics of CAPS patients reported to the Eurofever registry showed presence of rash in 97% of patients across the whole disease spectrum (3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study has identified 11 members of a single family with the clinical picture of MWS. The typical urticarial rash as a leading and the first symptom was present in all patients, similar to other reports (3, 12). Characteristics of CAPS patients reported to the Eurofever registry showed presence of rash in 97% of patients across the whole disease spectrum (3).…”
Section: Discussionsupporting
confidence: 91%
“…Disease symptoms had disappeared within hours to days from starting anakinra in all patients, which is in line with the published series (25). Improvement of hearing loss and amyloidosis was shown in individual patients when treatment was introduced early (12, 26). Rynne et al described reversibility of hearing loss in a 59 years-old woman with MWS but younger age might offer a window of opportunity for reversing hearing loss (26, 27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are a rich source of DAMPS [221,222] and their signalling molecules, such as ATP and formulated peptides (e.g., encoded by the NLRP3 gene), can induce inflammasome activation [221,223,224]. Mice with constitutively active NLRP3 have an overactive inflammasome pathway, which induces liver injury [225]. Additionally, increased ATP levels can propagate inflammation directly (via the P2X7 receptor in the inflammasome leading to increased IL-1β production) [226] and indirectly (via promotion of bacterial product entry into cells leading to activation of PAMPs) [227].…”
Section: Sterile Inflammation Toll-like Receptors and Propagation Ofmentioning
confidence: 99%
“…The Muckle Well Syndrome manifests during childhood and adolescence by recurrent febrile episodes associated with vanishing non-pruritic urticarial rash, arthralgia, myalgia and conjunctivitis. 5 , 7 , 11 , 13 , 14 , 22 Fever may not be present. 2 Symptoms tend to last longer than in FCAS (12 to 36 hours).…”
Section: Urticarial Exanthemamentioning
confidence: 99%